Pengaruh Pendekatan Pendidikan Matematika Realistik Berbasis Etnomatematika terhadap Komunikasi Matematis Siswa Sekolah Dasar - Suci Nooryanti; Sri Utaminingsih; Henry Suryo Bintoro (Universitas Muria Kudus, 2020)
The purposive of this study are (1) the average mathematical communication abilities of students who have learned by applying the ethnomatemics-based Realistic Mathematics Education approach, (2) the mastery of learning mathematical communication abilities of students who are taught with the Mathematics-Based Realistic Mathematics approach. This type of research is quantitative with true experimental design research design using the form of Posttest Only Control. The sample uses a simple random sampling technique and is carried out in class V SD 5 Jepang as an experimental class and class V SD 1 Gulang as a control class. Data collection techniques are tests of students' mathematical communication abilities. Data analysis techniques in this study include normality test, homogeneity test, average difference test and learning completeness test. The results showed that (1) the average mathematical communication ability of the experimental class students was higher than the average mathematical communication ability of control class students with expository learning; (2) students' mathematical communication abilities with ethnomatemicsbased Realistic Mathematics Education approach achieve mastery learning.